Anatomia comparativa das raízes de nove epífitas nativas do estado do Paraná - Herreiro, Samara Colaoto (2014)
The term epiphyte refers a large group of plants that live attached to the trunk, the branches and even the leaves of species known phorophytes. The classification of species of epiphytic habit involves morphoanatomical and physiological traits that enable them to survive under conditions of intermittent water. Although in the past the roots were seen with the basic function of attachment the plant to the substrate and absorb water and nutrients from the soil, with relatively stable internal organization, recently such function are associated with morphological and anatomical adaptations. Thus, the present study aimed to describe and compare the anatomical adaptations, characteristics of the epiphytic environment, present in the roots of Isochilus linearis, Maxillaria marginata, Oncidium flexuosum, Lophiaris pumila and Leptotes bicolor(Orchidaceae), Vriesea flava, Aechmea distichantha and Billbergia nutans (Bromeliaceae) and Philodendron propinquum(Araceae), native epiphytes from Araucaria Forest of Paraná State, Brazil. All orchids and the bromeliads V. flava and B. nutanswere classified holoepiphytes. The Bromeliaceae A. distichantha was classified optional epiphytes and the Araceae,P. propinquum, primary hemiepiphytes. The orchids species show roots with velamen, exodermis and endodermis differenciated from cortical parenchyma and polyarc vascular cylinder; bromeliads show velamen, cortex constituted by outer, middle and inner parenchyma and also polyarc vascular cylinder, whilein the P. propinquum roots was find uniseriate epidermis, exodermis and endodermis clearly distinct from cortical parenchyma and polyarc vascular cylinder. The anatomical features related to the epiphytic habitat observed in the studied species were: velamen, exodermis and endodermis thick, tilosome, tracheoidalelements, idioblasts with raphides and aerenchyma.